2021
DOI: 10.1038/s41598-021-91990-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between ankle brachial index and development of postoperative intensive care unit delirium in patients with peripheral arterial disease

Abstract: Patients with vascular diseases are prone to developing postoperative delirium (POD). Ankle brachial index (ABI) is a non-invasive clinical indicator of lower-extremities peripheral arterial disease (PAD) and has been identified as an indicator of cognitive impairment. We investigated the association between ABI and POD. 683 PAD patients who underwent elective leg arterial bypass surgery between October 1998 and August 2019 were collected for retrospective analysis. Demographic information, comorbidities, preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Moreover, the ORs follow that of the most-weighted study (Kotfis et al 2019 for the HF and Kotfis et al 2018 for the PVD), the exclusion of which in the sensitivity analysis led to no-longer statistically significant results. Finally, as HF and PVD have also been reported as risk factors for delirium in non-stroke patients [ 83 , 84 ], further studies are needed for a robust generalizability of the role of these two factors in PSD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ORs follow that of the most-weighted study (Kotfis et al 2019 for the HF and Kotfis et al 2018 for the PVD), the exclusion of which in the sensitivity analysis led to no-longer statistically significant results. Finally, as HF and PVD have also been reported as risk factors for delirium in non-stroke patients [ 83 , 84 ], further studies are needed for a robust generalizability of the role of these two factors in PSD.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral arterial disease (PAD) has been associated with underlying cerebrovascular disease [43]. Patients with PAD undergoing elective lower extremity bypass surgery were found to have a greater incidence of POD with more advanced PAD, measured by both lower ankle-brachial index values and higher Rutherford class [44]. The above vascular and cardiothoracic surgery investigations have both demonstrated that a disturbance in cerebrovascular perfusion has been associated with POD and lend credence to a microemboli or watershed stroke theory being involved with the etiology of POD (Figure 1).…”
Section: Microemboli or Watershed Strokementioning
confidence: 99%